EXPLORING ENVIRONMENTAL SUSTAINABILITY IN TERI MEDAN PRODUCTION: AN ECOLINGUISTIC PERSPECTIVE ON TOURIST SOUVENIRS - Puji Hariati; Purwarno Purwarno (English Review: Journal of English Education, 2025)
This study investigates the environmentally sustainable production methods of Teri Medan, a popular anchovy product from Medan, Indonesia, which has become an eco-conscious souvenir distributed through local markets and Micro, Small, and Medium Enterprises (UMKM). The research problem centers on how Teri Medan production integrates sustainable practices and how these are reflected in local cultural narratives. Using a descriptive qualitative approach, data were gathered through field observations, in-depth interviews, and document analysis. The study employs an ecolinguistic framework, which analyzes the language used to describe and communicate environmental values in the production process. Ecolinguistics, a discipline that examines the relationship between language and the environment, provides tools for identifying key cultural terms and narratives that convey sustainability practices. Findings reveal that Teri Medan production emphasizes sustainability across various stages, from selective fishing techniques, such as the use of gill nets that protect marine ecosystems, to eco-friendly methods in washing, boiling, sun-drying, sorting, and packaging. These practices not only minimize environmental impact but also enhance Teri Medan’s role as a cultural symbol of Medan’s commitment to environmental stewardship. The study highlights how promoting Teri Medan as a souvenir that embodies local traditions and sustainable values can contribute to the growth of sustainable tourism and serve as a model for eco-friendly souvenir production, aligning with global trends in responsible tourism.